PERAN LOYALITAS CREW TERHADAP PRESTASI KERJA CREW EVENT ORGANIZER CELTIC CREATIVE SURABAYA - Maria Mercedez Permata Putri (Perpustakaan Universitas Surabaya, 2018)
Human resources are an important asset for an enterprise because through their existing activities in the enterprise can run. This study aims to improve understanding of the role of loyalty on employee performance in the event organizer. This study is basic research that is conducted by using a qualitative approach. This study uses research object an event organizer in Surabaya, which is one business entity engaged in services, particularly services of organizing the event. Data collection methods used to obtain data that is by interview, observation, and analysis of internal company documents. The results of this study indicate that the role of loyalty greatly affect the performance of the crew to produce a good performance.